IDEAS AND INEQUALITY: REASSESSING FREEDOM AND POWER IN THE UNITES STATES - Holden, Shane N. (Young Scholars Grinchenko – Seton International Journal, 2026)
This paper examines the contradictions between the foundational ideals of the United States and the realities of its historical and contemporary practices. While the nation was established on principles of liberty, equality, and individual rights, these values have been selectively applied. This paper further explores how U.S. foreign policy and globalization have extended these inequalities far beyond domestic borders. Ultimately, this study demonstrates that the country’s definition of freedom has been continuously shaped to preserve political and economic dominance, raising critical questions about the alignment between American ideals and lived realities.